NEURAL TUBE DEFECT REPAIR AND VENTRICULOPERITONEAL SHUNTING: INDICATIONS AND OUTCOME - Shandip K Sinha; Anjan Dhua; Mohit Kumar Mathur; Sudhir Singh; Manoj Modi; Simmi K Ratan (EL-Med-Pub, 2012)
Neural tube defect with its global involvement of nervous system has lot of implications. There is cotroversy in terms of timing of repair, simultaneous or metachronous ventriculoperitoneal shunt and criteria for shunt surgery in neonatal age. We are reporting our approach and results of management of this disease in neonatal period.